2019
DOI: 10.4155/fsoa-2018-0096
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of Hydroalcoholic Extracts of Origanum Vulgare , Hypericum Perforatum and Their Active Components Carvacrol and Hypericin Against Staphylococcus Aureus

Abstract: Aim:This study was designed to evaluate the synergistic activities of hydroalcoholic extracts of medicinal plants Origanum vulgare and Hypericum perforatum and their active components, carvacrol and hypericin against Staphylococcus aureus.Methods:The synergistic effects of the plants, as well as carvacrol and hypericin, were examined using a checkered method against S. aureus (ATCC 12600).Results:A fractional inhibitory concentration of 0.5 was obtained for combination of O. vulgare and H. perforatum and 0.49 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…The plant has anti-inflammatory, antibacterial, antioxidant, anticancer, analgesic and neuroprotective as well as wound healing effects [25]. Spathulenol, caryophyllene oxide, linalool, alpha-terpineol, trans-caryophyllene and geraniol alpha-phellandrene, beta-myrcene and trans-caryophyllene can be active ingredients of these two plants that have the above-mentioned therapeutic effects [26][27][28][29][30][31][32][33]. Studies have shown that medicinal plants have both traditional and modern research with the use of stand-alone medicinal and therapeutic effects and their beneficial effects through their active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…The plant has anti-inflammatory, antibacterial, antioxidant, anticancer, analgesic and neuroprotective as well as wound healing effects [25]. Spathulenol, caryophyllene oxide, linalool, alpha-terpineol, trans-caryophyllene and geraniol alpha-phellandrene, beta-myrcene and trans-caryophyllene can be active ingredients of these two plants that have the above-mentioned therapeutic effects [26][27][28][29][30][31][32][33]. Studies have shown that medicinal plants have both traditional and modern research with the use of stand-alone medicinal and therapeutic effects and their beneficial effects through their active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely claimed that when food ingredients are mixed rather than using a single material, the synergistic therapeutic effects due to the combination of biochemicals may be superior to that of single biochemicals [ 20 , 21 ]. Much research has reported that when the mixed material is treated, a more effective bioactive effect is exhibited than when a single material is treated [ 22 , 23 , 24 ]. In this study, we aimed to establish a mixing ratio that dramatically enhanced immune function by utilizing two natural resources of Jeju, FES and SQN.…”
Section: Introductionmentioning
confidence: 99%
“…Stomach ache is often accompanied by certain symptoms including fever, vomiting, loss of appetite, inability to eat, and cramps. [13][14][15][16][17][18]. Recent documents showed that gastrointestinal problems such as stomach aches or stomach upset can be treated with medicinal plants [7].…”
Section: Introductionmentioning
confidence: 99%